Validação e aplicação de método para análise de pesticidas em água para consumo humano de dourados (ms) por CLAE/UV e CG/DTE - Lopes, Mara Nilza Todoro; Netto, Pedro Toledo [UNESP]; Lourencetti, Carolina; Marchi, Mary Rosa Rodrigues de [UNESP]; Ribeiro, Maria Lucia (Universidade Federal do Paraná, 2011)
Indiscriminate and inappropriate use of pesticides in agriculture has been pointed out for increasing health problems and environmental damage. Considering that water resources are the principal destiny of those compounds after application, the present study presents optimization and validation of two simple and effi cient analytical methods for pesticides quantifi cation in both surface and groundwater. Were selected the pesticides more commonly used at Dourados (MS - Brazil), region with intense agricultural activity. Pesticides were preconcentrated by solid-phase extraction using C18 (500 mg) cartridges and then divided in two groups for elution and quantifi cation: 2.4-D and 2.4-DCP were eluted with methanol and quantifi ed by high performance liquid chromatography with ultra-violet detector (HPLC-UV) while atrazine, DIA, DEA, trifl uralin and methyl parathion were eluted with ethylacetate (1:1, v/v) and quantifi ed by gas chromatography with thermionic specifi c detector (GC-TSD). The methods showed satisfactory accuracy (76-107%) and precision (<12%) for the substances analyzed at the fortifi ed levels selected for the study, except for DIA (<51%). Study of pesticide stability also presented good results: C18 cartridges could be stored for at least for 21 days at -20ºC with no signs of the compounds degradability. Both methods limits of quantifi cation of the pesticides (0.22 - 0.48 μg L-1) are in accordance to the levels currently established by the Brazilian national legislation for pesticides in water. Although only the pesticide 2.4-D has been detected in two distinct collection points in the study period of time, this work warns for the requirement of systematical analysis of pesticides presence in water destined to human consume, principally in areas of intense agriculture activity. Such monitoring can provide subsidies for public environmental policies.

O uso inadequado de pesticidas na agricultura tem sido apontado como fonte de risco para a saúde humana e para o ambiente. Considerando que os recursos hídricos são os principais destinos desses compostos após a aplicação, este trabalho apresenta a otimização e validação de dois métodos analíticos simples e efi cientes para a determinação de pesticidas em águas superfi ciais e subterrâneas. Foram selecionados os pesticidas mais aplicados no município de Dourados, (Mato Grosso – Brasil) com intensa atividade agrícola. Efetuou-se a pré-concentração por extração em fase sólida com cartucho C18 (500 mg) e eluição com metanol para as amostras analisadas por cromatografi a a líquido de alta efi ciência com detector espectrofotométrico na região do ultravioleta (CLAE/ UV) (2,4-D e 2,4-DCF) e com acetato de etila:diclorometano (1:1, v/v) para as analisadas por cromatografi a a gás com detector termiônico específi co (CG/DTE) (atrazina, DIA, DEA, trifl uralina e parationa metílica). Os métodos apresentaram exatidão (76-107%) e precisão (<12%) satisfatórias para as substâncias nos níveis de fortifi cação selecionados, exceto para DIA (<51%), assim como para o estudo de estabilidade dos pesticidas (-20ºC por até 21 dias). Os limites de quantifi cação dos métodos (0,22 - 0,48 μg L-1) estão de acordo com a legislação brasileira vigente para pesticidas em água. Embora somente o 2,4-D tenha sido detectado em dois pontos de coleta no período estudado, alerta-se para a necessidade de avaliação sistemática da presença de pesticidas em água para consumo humano, particularmente, em regiões com intensa atividade agrícola. Tal monitoramento pode fornecer subsídios para políticas públicas ambientais.
Validation and application of method for pesticides analysis in drinking water from dourados (ms - brazil) by hplc-uv and gc-tsd
Keywords: Validação; Pesticidas; Clae/uv; Cg/dte; Água - consumo humano; Validation; Pesticides; Hplc-uv; gc-tsd; Drinking water